Characteristic of KEY-like bacteriophages of Erwinia amylovora - Boyko А.А.; Zhuminska G.І.; Kushkina А.І.; Ivanytsya V.О.; Tovkach, F.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
The study of the heterogeneity of phage isolates obtained from twigs and leaves of pear affected with Erwinia amylovora is conducted. It is established that the isolate contains a two-component population of KEY-like phage particles, which differ in affinity for DEAE-cellulose. Phages of both subpopulations are represented by virions of B1 morphotype (Siphoviridae family) with regular icosahedral capsids with a diameter of about 77 nm and a length of the caudal appendages close to 172 nm. These phage particles are similar to those of the prototype KEY phage in morphology and size. According to the restriction analysis data, the genomes of the pure line phages KEY/7 and KEY/25 are similar to each other and have a size of about 72 kb, which is 25-27 % less than the size of the genome of KEY phage. It is assumed that the phages KEY/7 and KEY/25 represent deletion variants of KEY phage.